1998
DOI: 10.1159/000015865
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility in Ultrasonic Characterization of Carotid Plaques

Abstract: Background and Purpose: Echolucent carotid plaques compared with echogenic plaques could carry a significant risk of transient ischemic attacks and strokes, but the reproducibility of new ultrasonic methods has not yet been proved. The objective was to evaluate interobserver and intraobserver agreement in characterizing the carotid plaques studied by both B mode imaging and color Doppler imaging, which is the only ultrasonic method available for recognizing anechoic lesions. Methods: Fifty-three carotid plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 9 publications
1
26
1
2
Order By: Relevance
“…We enrolled 66 patients with a first-ever ischemic stroke who clinically showed a large-artery infarction 10 and ultrasonographic (Philips IU22 ultrasound system) evidence of ipsilateral ICA occlusion [11][12][13] due to arterial dissection detected within 12 hours from symptom onset. All subjects underwent (1) brain and neck magnetic resonance angiography combined with T1-weighted axial cervical magnetic resonance scans with the fat-saturation technique required to confirm the diagnosis of arterial dissection 14 ; (2) brain computed tomography; (3) careful neurologic evaluation; (4) cardiologic examination, ECG, and transthoracic echocardiography to rule out cardioembolic sources; and (5) complete blood chemistry analysis, including homocysteine.…”
Section: Methodsmentioning
confidence: 99%
“…We enrolled 66 patients with a first-ever ischemic stroke who clinically showed a large-artery infarction 10 and ultrasonographic (Philips IU22 ultrasound system) evidence of ipsilateral ICA occlusion [11][12][13] due to arterial dissection detected within 12 hours from symptom onset. All subjects underwent (1) brain and neck magnetic resonance angiography combined with T1-weighted axial cervical magnetic resonance scans with the fat-saturation technique required to confirm the diagnosis of arterial dissection 14 ; (2) brain computed tomography; (3) careful neurologic evaluation; (4) cardiologic examination, ECG, and transthoracic echocardiography to rule out cardioembolic sources; and (5) complete blood chemistry analysis, including homocysteine.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis included both carotid and femoral arteries. To determine plaque calcification, a semiquantitative method previously described by de Bray et al (24) was used.…”
Section: Carotid and Femoral Ultrasoundmentioning
confidence: 99%
“…15 Fisher et al 16 found that histologically validated ulceration was more common in endarterectomy specimens from patients with symptomatic carotid stenosis versus asymptomatic stenosis. De Bray et al 17 found that the reproducibility of detection of ulceration by 2D ultrasound was only 0.41. Schminke et al 5 reported that they could reliably follow progression or regression of ulceration by 3D ultrasound.…”
Section: Discussionmentioning
confidence: 99%